Enhancing Reproductive Health and Sexually Transmitted Infection Prevention Awareness through Community Engagement - Sukarya, Wawang Setiawan; Mustifah, Etty Farida; Ujianti, Irena; Pangestu, Mulyoto (Sanus Medical Journal, 2024)
ntroduction The Thousand Islands, a popular tourist destination in DKI Jakarta Province, is facing a new challenge, namely the increasing concern about the transmission of Sexually Transmitted Infections (STIs) triggered by the increase in tourism visits. In response to this issue, a community service activity was carried out by the Faculty of Medicine at UHAMKA. Objective The aim of this activity is to raise awareness and knowledge in the community, particularly among educators in the Thousand Islands, about the dangers of and prevention against STIs and the importance of Reproductive Health Education. Method The partners in this community service activity are teachers in the Thousand Islands. A total of 30 teachers were involved in this training. The methods used involve training and counseling that incorporate direct training and open discussions. Data were collected through observations and field notes. Results The results of this activity include an increase in understanding and skills of teachers concerning Reproductive Health Education and STI prevention, which they can apply in educating students. Additionally, it was found that community awareness about the dangers of STIs also increased as a direct result of this activity. Conclusion The conclusion that can be derived from this activity is that appropriate education and training on reproductive health and the prevention of STIs for the community, specifically educators, can be an effective strategy in controlling STI transmission in tourist areas like the Thousand Islands. This activity also helps to strengthen the local health system in dealing with the challenge of STI transmission.